Livestock Support and Water Depletion in Turkey. Issue 1 (25th January 2023) - Schuenemann, Franziska; Hess, Sebastian
Abstract: Turkey serves as an important food hub for neighboring countries in the water‐scarce Middle East and North African region, and self‐sufficiency in agri‐food production is one of the country's major policy objectives. The Turkish government had therefore introduced various support measures for its inefficient livestock sector, including payments for irrigated fodder crops, which are likely to increase water depletion. To simultaneously assess the economic and environmental effects of these policies, we link an economy‐wide computable general equilibrium model of Turkey to a newly developed water footprint module. We find that removal of direct livestock support may not lead to large water savings, but may instead redirect irrigation water to higher value crops. Conversely, removal of fodder subsidies and overall efficiency improvements in livestock can lead to overall water savings and net economic gains. Plain Language Summary: Turkey is a major exporter of food for the dry Middle East and North African region, while the goal of the Turkish government is to become more independent of imported livestock products. The government therefore pays different subsidies to encourage production within Turkey's inefficient livestock sector. As part of this strategy, a subsidy is paid to fodder crops that are irrigated with an increasing amount of water, although water resources in Turkey are already under stress. We therefore develop a new methodology that combines an economic model of the Turkish economy with a new water footprint calculation tool. With this method, we assess how different types of subsidies affect water use in Turkey through economic linkages and livestock‐related policies. Our model results show that removal of subsidies which are directly paid to livestock producers would not much reduce irrigation water use. However, the valuable irrigation water would increasingly be used to produce high value export crops such as vegetables, rather than low value fodder crops. Moreover, the abolishment of subsidies directly paid to fodder crop producers and technical measures that spur productivity in the livestock sector can achieve both, a reduction in irrigation water use and better economic outcomes. Key Points: Removal of direct Turkish livestock support may not lead to large water savings but redirects irrigation water to higher value crops Removal of fodder subsidies shows the largest potential for water savings out of all scenarios Improvements to overall economic efficiency in Turkey's livestock sector lead to net economic gains without major effects on blue water use